2018
DOI: 10.1039/c8sc01833b
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic versus kinetic control in substituent redistribution reactions of silylium ions steered by the counteranion

Abstract: Substituent exchange reactions of silylium ions can be steered in opposite directions. The judicious choice of the hydrosilane and the counteranion enables the selective formation of either triaryl- or trialkylsilylium ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 45 publications
1
39
0
5
Order By: Relevance
“…Disilanes other than hexamethyldisilane were also tested in the model reaction with allylbenzene (Figure ). However, heteroleptic disilanes such as 1,1,2,2‐tetramethyl‐1,2‐diphenylsilane suffered from substituent redistribution . A tert ‐butyl group at the silicon atom(s) prevents this but, relying on dearylation, 1,2‐di‐ tert ‐butyl‐1,1,2,2‐tetraphenyldisilane did not participate; a stoichiometric experiment showed that Me 3 Si + [CHB 11 H 5 Br 6 ] − cannot facilitate the dearylation step.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disilanes other than hexamethyldisilane were also tested in the model reaction with allylbenzene (Figure ). However, heteroleptic disilanes such as 1,1,2,2‐tetramethyl‐1,2‐diphenylsilane suffered from substituent redistribution . A tert ‐butyl group at the silicon atom(s) prevents this but, relying on dearylation, 1,2‐di‐ tert ‐butyl‐1,1,2,2‐tetraphenyldisilane did not participate; a stoichiometric experiment showed that Me 3 Si + [CHB 11 H 5 Br 6 ] − cannot facilitate the dearylation step.…”
Section: Methodsmentioning
confidence: 99%
“…However, heteroleptic disilanes such as 1,1,2,2-tetramethyl-1,2-diphenylsilane suffered from substituent redistribution. [12] A tertbutyl group at the silicon atom(s) prevents this but, relying on dearylation, 1,2-di-tert-butyl-1,1,2,2-tetraphenyldisilane did not participate;as toichiometric experiment showed that Me 3 Si + [CHB 11 H 5 Br 6 ] À cannot facilitate the dearylation step. Notably,u nsymmetrically substituted 1-isopropyl-1,1,2,2,2pentamethyldisilane furnished both regioisomers of the bissilylated alkane with a6 2:38 ratio in 47 %c ombined yield.…”
mentioning
confidence: 99%
“…Only silyl cations containing three identical substituents or ab ulky tert-butyl group were employed to avoid any substituent redistribution during its generation. [14] In contrast to the kinetically stabilized silylium ion 1a,s ilyl cations 1b-1d are stabilized through coordination by the chlorinated aromatic solvent, which is immediately replaced upon addition of the phosphane,t hereby forming classical Lewis pair adducts.Notably,t hese silylphosphonium salts [15] were found to undergo aS ET as shown for the free silylium ion 1a (Table 1, entries 4-7). Tr eatment of solvent-stabilized silylium borates [1b-d(odcb)][B(C 6 F 5 ) 4 ]with an equimolar amount of Mes 3 P( 2b)i mmediately resulted in ab luish purple solution (l max = 574 nm), again indicating the presence of radical intermediates.T he EPR spectra of the solutions showed the typical doublet of phosphoniumyl radical cation 3b (see Figure 1d for the reaction of [1b(odcb)] with phosphane 2a and the Supporting Information for the reactions of [1bd(odcb)] with phosphane 2b).…”
mentioning
confidence: 99%
“…Neben Hexamethyldisilan wurden auch andere Disilane in der Modellreaktion mit Allylbenzol getestet (Abbildung ). In heteroleptischen Disilanen wie 1,1,2,2‐Tetramethyl‐1,2‐diphenylsilan findet jedoch eine Umverteilung der Substituenten statt . Eine tert ‐Butylgruppe an den Siliciumatomen verhindert das, aber 1,2‐Di‐ tert ‐butyl‐1,1,2,2‐tetraphenyldisilan nahm gar nicht an der Reaktion, hier der Dearylierung, teil; ein stöchiometrisches Experiment zeigte, dass Me 3 Si + [CHB 11 H 5 Br 6 ] − den Dearylierungsschritt gar nicht vermittelt.…”
Section: Methodsunclassified
“…In heteroleptischen Disilanen wie 1,1,2,2-Tetramethyl-1,2-diphenylsilan findet jedoch eine Umverteilung der Substituenten statt. [12] Eine tert-Butylgruppe an den Siliciumatomen verhindert das,a ber 1,2-Di-tert-butyl-1, DFT-Rechnungen wurden auf dem Niveau PW6B95-D3/ def2-QZVP + COSMO-RS(Chlorbenzol)//TPSS-D3/def2-TZVP + COSMO(Chlorbenzol) [13] [14] Die reaktionsträge Si-Si-Bindung in Hexamethyldisilan wird in der Regel durch Übergangsmetallkomplexe [2] oder im Verlauf eines übergangsmetallkatalysierten Prozesses aktiviert. [4] Dessen intermolekulare Addition an nichtaktivierte Alkene ist gänzlich unbekannt.…”
Section: Angewandte Chemieunclassified